EFEKTIVITAS TEKNIK PROBLEM BASED INTRODUCTION TERHADAP AKTIVITAS BELAJAR SISWA KELAS IV PADA MUATAN IPS - Rahmawati, Sri; Tahir, M.; Oktaviyanti, Itsna (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2018)
This stady aims to determine de “effecriveness of de problrm based introduction learning techque in learing activities of class IV IPS SDN 20 Cakranegara in cakranegara” subdistrict. This type of recearc is an experimental research wth non eguivalent control graoup design type. The researchsubjects were 48 students, 24 in the experimental class and 24 in the control class. Data collection techniques in this study used observation and questionnaires. Based on the results of the post-test the average value of students in the experimental class higher compared to the average value of students in the control class. the average value of students in the experimental class post-testwas 80 while the average value of students in the control class was 66. This acquisition was futher strengthened by the results of the hypothesis testwith the formula t-pillan variance. Analisis of the calculation obtained tcount result of 7,838 while ttable, og 2,410 at a significant level of 5% which means that the result of tcount ≥ ttable, so that it can be concluded that Ha is acceptes and H0 is re jected which reads “effecriveness of de problrm based introduction learning techque in learing activities of class IV IPS SDN 20 Cakranegara in cakranegara”.